Interface Engineering Boosting High Power Density and Conversion Efficiency in Mg2Sn0.75Ge0.25‐Based Thermoelectric Devices - Wu, Xinzhi; Lin, Yangjian; Liu, Chengyan; Han, Zhijia; Li, Huan; Wang, Yupeng; Jiang, Feng; Zhu, Kang; Ge, Binghui; Liu, Weishu (Advanced energy materials, 2023)
Electrode contact interfaces for practical thermoelectric (TE) devices require high bonding strength, low specific contact resistivity, and superb stability. Herein, the state‐of‐the‐art Cu2MgFe/Mg2Sn0.75Ge0.25 interface is designed for Mg2Sn0.75Ge0.25‐based TE devices, adhering to the general strategy of high bonding propensity, thermal expansion matching, diffusion passivation, and dopant inactivation. The interfacial stability is verified by the in situ transmission electron microscopy analysis, thereby confirming the contributions from decreasing the chemical potential gradient and increasing the diffusion activation energy barrier. The single‐leg device exhibits a high power density (ωmax) of 2.6 W cm−2 and conversion efficiency (ηmax) of 8% under a temperature difference (ΔT) of 370 °C, which is the record‐breaking value in comparison to other Mg2(Si, Ge, Sn)‐based TE devices. Additionally, a two‐couple device with p‐type Bi2Te3 shows an excellent ωmax of 1.3 W cm−2 and ηmax of 5.4% under a ΔT of 270 °C, comparable to commercial Bi2Te3 devices. The proposed interface design strategy provides a general technique for constructing high‐performance devices using cutting‐edge TE materials. Cu2MgFe thermoelectric interface material (TEiM) is designed, following a general strategy, i.e., considering high bonding propensity, thermal expansion matching, diffusion passivation, and dopant inactivation. The Mg2Sn0.75Ge0.25 TE device exhibits a high‐power density of 2.6 W cm−2 and a conversion efficiency of 8% under a temperature difference of 370 °C. The TEiM design strategy bridges high‐performance TE materials and devices.